2021
DOI: 10.3390/ijms22020576
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Dependence in Extensively Drug-Resistant Acinetobacter baumannii Strain Is Associated with ISAjo2 and ISAba13 Insertions and Multiple Cellular Responses

Abstract: The nosocomial opportunistic Gram-negative bacterial pathogen Acinetobacter baumannii is resistant to multiple antimicrobial agents and an emerging global health problem. The polymyxin antibiotic colistin, targeting the negatively charged lipid A component of the lipopolysaccharide on the bacterial cell surface, is often considered as the last-resort treatment, but resistance to colistin is unfortunately increasing worldwide. Notably, colistin-susceptible A. baumannii can also develop a colistin dependence aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Decreased levels of BamA and multiple other OM proteins were also observed with JB-95 (LptD inhibitor) treatment in E. coli ( 22 ). Similarly, downregulation of MlaA and LptD proteins was observed concurrently in LPS-deficient Acinetobacter baumannii ( 53 ).…”
Section: Discussionmentioning
confidence: 93%
“…Decreased levels of BamA and multiple other OM proteins were also observed with JB-95 (LptD inhibitor) treatment in E. coli ( 22 ). Similarly, downregulation of MlaA and LptD proteins was observed concurrently in LPS-deficient Acinetobacter baumannii ( 53 ).…”
Section: Discussionmentioning
confidence: 93%
“…For example, it was observed (15) that an IS 1202 -related IS was implicated in the deletion of the capsular polysaccharide locus ( cps ), the major known Streptococcus pneumoniae virulence factor, important for Streptococcal survival in the blood and strongly associated with antiphagocytic activity (16). While Chamoun et al (17) showed that insertion of IS Ajo2 into the lpxA gene, involved in lipid A biosynthesis, can result in colistin dependence which, they suggest, possibly leads to colistin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…N. gonorrhoea strains from geographically distinct areas and different years (clinical isolates from Baltimore, 1991–1994, clinical isolates from Seattle, 2011–2013 and WHO 2016 reference strains) have different MlaA levels, whereas many clinical isolates of non-typeable H. influenzae have lower levels of MlaA [ 14 , 63 ]. Furthermore, in a study comparing an A. baumannii colistin-susceptible clinical isolate to its colistin-dependent subpopulation, downregulated expression of proteins involved in the maintenance of OM asymmetry, including MlaA, was observed in the latter isolates [ 102 ].…”
Section: Mlaa An Om Lipoprotein Of the Mla Systemmentioning
confidence: 99%